Tracking the Continuous Evolutionary Processes of an Endogenous Retrovirus of the Domestic Cat: ERV-DC - Kawasaki, Junna; Nishigaki, Kazuo (Viruses, 2018)
An endogenous retrovirus (ERV) is a remnant of an ancient retroviral infection in the host genome. Although most ERVs have lost their viral productivity, a few ERVs retain their replication capacity. In addition, partially inactivated ERVs can present a potential risk to the host via their encoded virulence factors or the generation of novel viruses by viral recombination. ERVs can also eventually acquire a biological function, and this ability has been a driving force of host evolution. Therefore, the presence of an ERV can be harmful or beneficial to the host. Various reports about paleovirology have revealed each event in ERV evolution, but the continuous processes of ERV evolution over millions of years are mainly unknown. A unique ERV family, ERV-DC, is present in the domestic cat (Felis silvestris catus) genome. ERV-DC proviruses are phylogenetically classified into three genotypes, and the specific characteristics of each genotype have been clarified: their capacity to produce infectious viruses; their recombination with other retroviruses, such as feline leukemia virus or RD-114; and their biological functions as host antiviral factors. In this review, we describe ERV-DC-related phenomena and discuss the continuous changes in the evolution of this ERV in the domestic cat.